Politeness in Utterance of Pasambahan Batagak Pangulu in Minangkabau Ethnic - Mac Aditiawarman; Gusri Dozan (Fakultas Sastra Universitas Ekasakti, 2023)
Language is a tool used by humans to interact and cooperate with other people. Language also strengthens the relationship between people and their culture, so that a culture can be recognized and maintained. Minangkabau culture always preserves oral traditions such as the pasambahan utterance which is a form of utterance conveyed by both parties in finding solutions or overcoming problems. This research uses a qualitative descriptive method to explore politeness, and the data analysis method used in this research is the equivalent method with referential and transitional determinants, collecting data using observation, documentation, and interview techniques. Then, the data is analyzed by using the technique of sorting the determining element with the distinguishing power of courage. This research uses Leech's theory in finding the maxim and politeness scale. The results of this research indicate that there are politeness maxims and politeness scales in the utterance of pasambahan batagak pangulu in Minangkabau. The maxims obeyed in this speech are 42 and the politeness scale is 42. The forms of politeness maxim compliance found in the pasambahan utterance consist of 10 tact maxims, 2 maxims of generosity, 9 approbation maxims, 10 maxims of modesty, 9 maxims of agreement and 2 maxims of sympathy. The forms of politeness scale found in pasambahan utterances consist of 35 cost-benefit, 10 optional, and 7 indirectness.